Ethnopharmacology, Biological evaluation and Chemical composition of Boswellia dalzielii Hutch: A Review - Abdulrahman Mahmoud Dogara; Abubakar Abdullahi Lema; Harmand A. Hama; Saber Hamad; Nor Hasima Mahmod Mohammad; Mohammad Moneruzzaman Khandaker; Wandayi Emmanuel Amlabu (Indonesian Journal of Pharmacy, 2022)
The Burseraceae family consists of 18 genera and 540 species. Boswellia dalzielii is a medicinal plant used in tropical and subtropical areas for the treatment and management of various ailments. Despite the medicinal value of B. dalzielii, there is no comprehensive documentation. The study aimed to review the ethnopharmacology, biological evaluation and chemical composition of B. dalzielii. Scopus, Web of Science, BioMed Central, Science Direct, PubMed, Springer Link, and Google Scholar were searched to find published articles. The results showed that the leaves, stem bark, and root of B. dalzielii have been traditionally used in Nigeria, Cameroon, Burkina Faso, Benin, Sudan, and Guinee for the treatment and management of antirheumatic, antispasmodic, analgesic, antiseptic, hypotensive, malarial mental illness, ulcer, pain, and fever. It is also found that leaves, stem bark, and root have antioxidant, antibacterial, antifungal, and antimalarial properties with stembark having the highest activity. Chemically, it was revealed the leaf has high contents of monoterpenes hydrocarbons with alpha-pinene as the major compound. The species were largely studied in vitro, according to the literature survey. A well-designed clinical experiment is required to obtain conclusive evidence on the efficacy of stembark. The standard dose and safety of the stembark should be established.